2006
DOI: 10.1373/clinchem.2006.069286
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Identification of Clinically Important Bacteria by High-Resolution Melting Analysis after Broad-Range Ribosomal RNA Real-Time PCR

Abstract: Background: Broad-range PCR provides valuable information for detecting bacterial infections. This study assesses the combined use of broad-range real-time PCR and high-resolution melting analysis for rapid detection and identification of clinically important bacteria. Methods: We subjected 46 bacterial culture colonies representing 25 clinically important bacterial species to LightCycler real-time PCR amplification of the 16S rRNA gene in the presence of LCGreen I fluorescent dye. We performed high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 30 publications
1
103
0
3
Order By: Relevance
“…Also, high-resolution melting (HRM) curve analysis without using a fluorescence hybridization probe has been introduced recently as a rapid technique for genotyping and mutation scanning (Gundry et al, 2003). The introduction of new fluorescent dyes, such as LCGreen I and SYTO 9 green (Krypuy et al, 2006;Monis et al, 2005), has brought further improvement to HRM curve analysis for clinical (Reed & Wittwer, 2004;Wittwer et al, 2003;Zhou et al, 2005) and/or epidemiological (Cheng et al, 2006;Odell et al, 2005;Robinson et al, 2006) investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, high-resolution melting (HRM) curve analysis without using a fluorescence hybridization probe has been introduced recently as a rapid technique for genotyping and mutation scanning (Gundry et al, 2003). The introduction of new fluorescent dyes, such as LCGreen I and SYTO 9 green (Krypuy et al, 2006;Monis et al, 2005), has brought further improvement to HRM curve analysis for clinical (Reed & Wittwer, 2004;Wittwer et al, 2003;Zhou et al, 2005) and/or epidemiological (Cheng et al, 2006;Odell et al, 2005;Robinson et al, 2006) investigations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods require separate DNA amplification procedures and sophisticated equipment that are not always available on a routine basis. Recently, real-time PCR combined with high-resolution melting analysis has also been explored for rapid bacteria identification (25 ). In all, 25 clinically important bacterial species could be identified after LightCycler real-time PCR amplification of the 16S rRNA gene in the presence of LCGreen I fluorescent dye followed by high-resolution melting analysis of the PCR products with the HR-1 instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of broad-range bacterial species identification, Klaschik et al 22 were the first to develop a PCR and melting analysis assay using 2 probes for identification of 17 common bacterial species. In 2006, Cheng et al 23 differentiated and identified 46 bacterial culture colonies representing 25 clinically important species using a LightCycler real-time PCR instrument for amplification of the 16S rRNA gene in the presence of the LC Green I fluorescent dye and a HR-1 melting instrument for melting profiles, without using any probe. Simplicity and smartness of this assay that promised rapid and economic bacterial species identification in future was instantly recognized and commented on in Editorial 24 .…”
Section: Melting Analysis For Species Identification Purposesmentioning
confidence: 99%